Developing skills for employability with German partners : 8 success stories from the health and geriatric care sector - Niediek, Silvia [Verfasser] (Bundesinstitut für Berufsbildung, 2015)
This edition of the brochure "Developing skills for employability with German partners" presents eight success stories of skill development in the health and geriatric care sector. It was realised in a joint effort by German and international partners. (BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; S 6.4.5 Gesundheits-, Sozial- und Erziehungsberufe; G 1.2.4.2.8 Gesundheits-, Veterinär- und Sozialwesen; Berufsbildung; Internationale Zusammenarbeit; Bildungsexport; Berufsfeld Gesundheit; Altenpflege